Antimicrobial and Phytochemical Analysis of Half-ripe Fruits of Aegle marmelos (l.) Correa Found in Butwal Area (Butwal Campus Journal, 2024)
In this work, the half-ripe fruit of Aegle marmelos found in the Butwal region was examined for antibacterial, phytochemical, and antioxidant activity as well as to quantify antioxidant activity, TPC, and TFC. Half-ripe A. marmelos fruits were collected from 12 to 24 April 2022 from Butwal area. Fruit pulp was shade-dried, crushed, and cold-macerated in methanol solvent to prepare methanolic extract. The crude extract was subjected to a preliminary phytochemical screening that found flavonoids, reducing sugar, polyphenols, alkaloids, steroids, tannins, terpenoids, coumarins, quinones, glycosides. The DPPH radical scavenging assay was used to evaluate the antioxidant activity, the agar well diffusion method was used to assess the antimicrobial activity, the Folin-Ciocalteu method was used to assess the total phenolic content, and the aluminum chloride colorimetric method was used to assess the flavonoid content. The DPPH radical scavenging activity in terms of IC50 of the fruit sample was 99.87±1.27µg/mL.   The total phenolic content (TPC) was found 88.55±6.71 (mg of GAE/g), total flavonoid content (TFC) was found 10.98±0.134 (mg of QE/ g). Upon antimicrobial test, the extract was sensitive to both gram-positive bacteria Staphylococcus aureus (ZOI= 10.4±0.75 mm) and gram-negative bacteria to Escherichia coli (ZOI=11.22±0.18mm) almost equally.